02Jan

все баллы за уравнение (x-2)(x-3)-x^2=(x+2)(x+4)+x^2-(x-1)^2

ilyhaaa Математика 2 8

все баллы за уравнение (x-2)(x-3)-x^2=(x+2)(x+4)+x^2-(x-1)^2

Posted by ilyhaaa | Posted at Jan 02, 2014 | Categories: Математика

Answers

Урсик
Урсик

x^2-3x-2x+6-x^2=x^2+4x+2x+8+x^2-(x^2-2x+1) -5x+6=2x^2+6x+8-x^2+2x-1 -5x+6=x^2+8x+7 x^2+13x+1=0 D=169-4=165 x1=(-13+sqrt(165))/2 x2=(-13-sqrt(165))/2

Jan 02, 2014 22:37
byka
byka

[latex](x-2)(x-3)-x^2=(x+2)(x+4)+x^2-(x-1)^2;\ x^2-5x+6-x^2=x^2+6x+8+x^2-x^2+2x-1;\ -5x+6=x^2+6x+8+2x-1;\ x^2+13x+1=0;\ D=13^2-4cdot 1=169-4=165;\ x_{1,2}=frac{-13pm sqrt{165}}{2}.[/latex]

Jan 02, 2014 22:38

Leave a answer